Eyeing up the pandemic: A literature review of the ocular manifestations of COVID-19 - Mardini, Ali; AbdulQadir, Seemal; Alhomsi, Khaled (Jordan Medical Journal, 2022)
Background Since the onset of SARS-CoV-2, this novel virus has been the focus of many studies seeking to improve the ability of healthcare systems to withstand pandemics against it. COVID-19 has pulmonary and cardiovascular implications, but its ocular effects remain a subject of debate. Objectives The objective of our narrative review is to explore the ophthalmic manifestations of COVID-19, identify research gaps, and act as a guide for further research in the field. Methods The literature search involved original studies published from January 1, 2020, up until August 20, 2021, on the PubMed database. Title and abstract screening and full text review were conducted by two independent researchers, with a third researcher resolving conflicts. Studies that met the set inclusion criteria were used for data synthesis. Results The preliminary search generated 59 articles, with 25 being data extracted. Conjunctivitis, epiphora and ocular irritation were consistently stated anterior segment manifestations. Posterior segment implications were mostly subclinical, including cotton-wool spots and retinal nerve-fiber layer thinning, but some cases were more detrimental, such as central retinal vein occlusion, posterior segment inflammation, retinal hemorrhages, and fungal infiltration. RT-PCR tests were unreliable in detecting SARS-CoV-2 infection in ocular tissues, potentially due to methodological limitations. Conclusion Anterior segment findings were significant manifestations of the novel coronavirus, but a clear resolution of posterior segment findings is yet to be made. In the absence of reliable COVID-19 ocular sample tests, all links made to SARS-CoV-2 etiology remain tentative; further research must be directed to the field with modified testing strategies.